(untitled) (Fiep Bulletin - online, 2014)
The present article shows the results of a survey presented as Final Paper from the Physical Education class at Centro Universitário Feevale in the year 2005. The investigated matter was: "What are the expectations from private high school students related to contents and practice to be performed in the physical education classes?" The main goal here was to learn and understand High School students’ perception about the activities and contents developed on the physical education classes, for helping in teaching practice. This survey was based on qualitative, interpretative, descriptive pattern and case study. The tools used to collect the data were: class observation, semi-structured interviews, field reporting and document analysis. The survey was accomplished in a private school in Taquara, Rio Grande do Sul, Brasil, with the cooperation of some High School students. The results showed that students expect to have physical education classes directed to the development of fitness for sports and they show their expectations concerning to class organization, methodology and professional teacher performance, activities and contents to be developed in high school classes.